Banking Stock Performance in the Conventional Banking Industry: An Examination Before and During Covid-19 Pandemic - Dewi Salmita; Afnan Bachmid; Sofyan Bachmid (Jurnal Ilmu Perbankan dan Keuangan Syariah, 2024)
The Covid-19 pandemic significantly impacted various economic sectors, including the banking industry, as a vital component of financial markets. Stock performance reflects a company's financial health and market perception, measured through stock returns. However, the extent to which the pandemic affected the stock performance of conventional banking companies in Indonesia remains underexplored, creating a critical research gap. This study aims to analyze and compare the stock performance of conventional banking companies listed on the Indonesia Stock Exchange (IDX) before and during the Covid-19 pandemic. Secondary data were collected from the stock returns of banking companies, covering the pre-pandemic period (2017–2019) and the pandemic period (2020–2022). Using purposive sampling, 39 companies were selected from a population of 44. The Wilcoxon Signed Rank Test was applied to test the hypothesis using SPSS 26 software. The findings reveal no statistically significant differences in stock performance between the pre-pandemic and pandemic periods (Z = -1.234, p = 0.217). These results highlight the resilience of Indonesia's conventional banking industry amidst the Covid-19 crisis.